Association Between Postoperative Nausea Severity and Pain Intensity in Patients Experiencing Postoperative Nausea and Vomiting After Minor Oral and Maxillofacial Surgery: A Retrospective Cohort Study - Yuta Horikoshi; Tina Nakamura; Masanori Tsukamoto; Fumika Ogata; Hiroshi Hoshijima; Hiroshi Nagasaka; Katsushi Doi; Tsutomu Mieda (Journal of Clinical Medicine, 2026)
Background: The relationship between postoperative nausea and vomiting (PONV) and postoperative pain (POP) has not yet been fully clarified. This investigation aimed to evaluate the association between postoperative nausea severity and the intensity of POP following minor oral and maxillofacial surgery (OMS) under general anesthesia. Methods: This retrospective cohort study reviewed data from patients aged 16 to 70 years who received general anesthesia with nasal intubation for minor OMS at our institution from January 2021 to August 2022; patients with pre-existing conditions influencing POP or PONV were excluded from the analysis. Predictor variables included nausea scores assessed with a 100 mm visual analog scale (VAS), with a secondary sub-analysis excluding asymptomatic patients. The primary and secondary outcomes were VAS-rated POP levels at early (2 h) and late and delayed (6 h and 24 h) time points post-surgery, respectively. Covariates encompassing patient demographics, anesthetic details, and surgical factors were adjusted for, with statistical significance defined as p < 0.05. Results: Out of the 160 patients analyzed, the PONV incidence rates were 20.0% (n = 32) at 0–2 h, 4.4% (n = 7) at 2–6 h, and 0% (n = 0) at 6–24 h. The results from the adjusted multivariate model analysis show that, in this cohort of 160 patients—regardless of the presence or absence of PONV—higher nausea severity was not significantly associated with a reduction in POP intensity at the 2 h mark in the primary analysis. However, in an exploratory subgroup analysis, in the 32 patients who experienced PONV at the 2 h time point, higher nausea severity was significantly associated with lower POP levels [regression coefficient = −0.45, 95% confidence interval = −0.77 to −0.14, p = 0.006]. Conclusions: These results demonstrate an inverse statistical association between nausea severity and POP intensity at 2 h within a small subgroup of 32 patients with PONV. However, these findings do not establish a causal relationship.